Analisis Pengaruh Bimbingan Konseling Islam Terhadap Pembentukan Karakter Religius Siswa di Sekolah - Tri Fajriah Humaira; Yuda Prasetya (Institut Agama Islam Negeri Curup, 2022)
In the field of Islamic counseling guidance is very important in the world of education, including one of them is an educator or a teacher in schools because almost all of them educate a student and contribute to forming a superior character and becoming a person who has better development in his life. In addition, students need an increase in the potential of religious characters in their school environment. Therefore, it is necessary to have innovations to implement and develop Islamic counseling guidance in cultivating the form of students' religious character in the school environment. In the implementation, it is something that has been designed well and thoroughly, and in the implementation of these innovations in accordance with the plans that have been agreed upon by other educators in guiding the character of students. It is hoped that with this journal, it is expected to be able to move the religious character of students through debriefing and Islamic counseling guidance which will later give birth to intelligent students and implement learning in everyday life with a religious character.